Supply Chain Management and Advanced Planning Concepts, Models, Software, and Case Studies - Stadtler, Hartmut; Kilger, Christoph; Meyr, Herbert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
Supply Chain Management, Enterprise Resources Planning (ERP), and Advanced Planning Systems (APS) are important concepts in order to organize and optimize the flow of materials, information and financial funds. This book, already in its fifth edition, gives a broad and up-to-date overview of the concepts underlying APS. Special emphasis is given to modeling supply chains and implementing APS successfully in industry. Understanding is enhanced by several case studies covering APS from various software vendors. The fifth edition contains updated material, rewritten chapters and an additional case study.
Introduction -- Part I: Basics of Supply Chain Management -- Part II: Concepts of Advanced Planning Systems -- Part III: Implementing Advanced Planning Systems -- Part IV: Actual APS and Case Studies -- Part V: Conclusion and Outlook -- Part VI: Supplement.
Keywords: Business logistics; Production management; Information technology; Business$1 (BData processing.s; Engineering economics; Engineering economy; Supply Chain Management; Operations Management; IT in Business; Engineering Economics, Organization, Logistics, Marketing